Oppositional Genealogy of Ḥanābilah towards al-Ma’mūn’s Miḥna Policy: Nomos and Authority Conflict - Muhammad Fahmi; Sholehan Sholehan; Ibnu Anshori; Ali Mas'ud; Senata Adi Prasetia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
While consolidating democracy in Muslim-majority countries like many Arab countries today, the problem of opposition between the people and the rulers still leaves a latent conflict. The opposition is not new in the Islamic world. In this context, the Ḥanābilah oppositional movement against the al-Ma'mūn's miḥna policy finds its significance here. The article aimed to determine the genealogy of the Ḥanābilah opposition to the al-Ma'mūn's miḥna policy and to correct the Weberian perspective in reading socio-religious movements, mainly the movement carried out by the Ḥanābilah ulema community by offering a socio-convergent perspective. This article is more a religious research than research on religion. The data in this study were sourced from books written by Ibn Ḥanbal and other relevant books. Data were analyzed using data display, data verification, and conclusions techniques. The results show that Ibn Ḥanbal's opposition to the miḥna is motivated by maintaining theological orthodoxy and protecting the authority of the Sunni ulema. Ḥanābilah's oppositional actions are more related to the conflict of authority. This convergence thesis is in line with the blurred approach of Edmund Burke and Adonis or the double-edged sword theory of Alberto Melluci. Opposition as part of efforts to construct a civilized political system which is not only seen from an opposing side but also as a sparring partner in carrying out the function of amr ma'rūf nahy munkar 'commanding right and forbidding wrong' to the government to realize good governance.